Visible-Light-Induced Radical Polynitration of Arylboronic Acids: Synthesis of Polynitrophenols - Zhang, Qi; Raveendra Babu, Kaki; Huang, Zhouliang; Song, Jinna; Bi, Xihe (Synthesis, 2018)
We report a visible light-assisted one-pot method for the synthesis of polynitrophenols through radical tandem hydroxylation and nitration of arylboronic acids by utilizing copper(II) nitrate trihydrate as the nitro source. This method features mild conditions, a simple procedure, and good functional group tolerance. Compared to conventional methods, this work provides a straightforward approach for the polynitration of aromatic compounds.
Keywords: polynitrophenols; visible light; arylboronic acid; nitration; copper